1989
DOI: 10.3109/02656738909140429
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of combined cisplatin and hyperthermia treatment for refractory malignancy

Abstract: Research in animal and human cell cultures has shown that some chemotherapeutic agents, cisplatin in particular, have cytotoxicity that is significantly potentiated at elevated temperatures. Concurrent administration of systemic cisplatin and local hyperthermia in human patients has not been previously reported. A phase I/II study was undertaken to assess the systemic and local toxicities and activity of concurrently administered local hyperthermia and systemic cisplatin in human tumours. Nine patients with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Thus, the application of deep local hyperthermia along with the systemic administration of cisplatin appears to be an attractive option in patients with recurrent pelvic cervical cancer. Once initial feasibility data regarding the clinical use of cisplatin and local hyperthermia combination treatment were reported (29), Rietbroek et al (7) published a phase II study of combined weekly locoregional hyperthermia and systemic cisplatin administration in patients with previously irradiated recurrent cervical carcinoma (30). Using a regimen of 50 mg of cisplatin per week with a one-week interruption following four cycles for a total of 12 cycles, corresponding to a projected dose intensity of 40 mg per week, these authors observed an overall response in 12/23 patients (52%; 95% confidence interval, 31–73%) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the application of deep local hyperthermia along with the systemic administration of cisplatin appears to be an attractive option in patients with recurrent pelvic cervical cancer. Once initial feasibility data regarding the clinical use of cisplatin and local hyperthermia combination treatment were reported (29), Rietbroek et al (7) published a phase II study of combined weekly locoregional hyperthermia and systemic cisplatin administration in patients with previously irradiated recurrent cervical carcinoma (30). Using a regimen of 50 mg of cisplatin per week with a one-week interruption following four cycles for a total of 12 cycles, corresponding to a projected dose intensity of 40 mg per week, these authors observed an overall response in 12/23 patients (52%; 95% confidence interval, 31–73%) (7).…”
Section: Discussionmentioning
confidence: 99%
“…The median survival was 9 / months identified SCC-Ag responders had developed clinical / 7b4e$$0921 02-11-97 08:46:26 canxa W: Cancer PD at last follow-up; in all four patients SCC-Ag in-use cisplatin and HT in a dose of 50 mg/m 2 /week for a period of 6 weeks. [26][27][28][29][30] Because the authors believed creased significantly. that 6 weekly cycles might not be sufficient for induction of worthwhile responses, they chose to treat pa-…”
Section: Squamous Cell Carcinoma Antigenmentioning
confidence: 99%
“…Clinically, the possibility of combining chemotherapy with local heating therefore looks more attractive. In fact, clinical phase 1-11 studies are already being performed investigating the combined action of local hyperthermia and cisplatin (3, [5][6][7].…”
mentioning
confidence: 99%